2013
DOI: 10.1186/1687-1499-2013-31
|View full text |Cite
|
Sign up to set email alerts
|

Power and rate allocation for video conferencing in cellular networks

Abstract: We consider resource allocation for semi-elastic applications such as video conferencing. We propose to model user utility as a sigmoid function of the average bit rate over multiple time slots. The goal is to maximize the total expected user utility over time through allocation of downlink power and subcarriers in each time slot. We propose resource allocation that considers both the average rate achieved so far and the future expected rate, and show how the future expected rate can be estimated by modeling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The Lagrange is (4) where , are the Lagrangian multipliers associated with the rate constraints which are interpreted as rate prices [29], and are the Lagrangian multipliers associated with the power constraints.…”
Section: A Resource Allocationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Lagrange is (4) where , are the Lagrangian multipliers associated with the rate constraints which are interpreted as rate prices [29], and are the Lagrangian multipliers associated with the power constraints.…”
Section: A Resource Allocationmentioning
confidence: 99%
“…The utility function for a classapplication is if else where is also expressed in units of 100 kb/s, , , , kb/s, , , , kb/s. Both utility functions are sigmoid [29]; we set the minimum rate requirements to the rate at the maximum average utility, which is given by kb/s and kb/s. The arrival processes are Poisson processes with intensities and , respectively, and the connection durations are exponentially distributed with means s and s, respectively.…”
Section: A Two Semi-elastic Classesmentioning
confidence: 99%
“…MPEG, utility should be represented as a sigmoid function of the average rate over each group-of-pictures [11]. Thus the algorithms in [3][4] [5][6] [7] are not suitable to video conferencing.…”
Section: Introductionmentioning
confidence: 99%
“…A key resource allocation design problem consists of how to consider a user's current channel and likely future channels. In [11], we considered the case in which utility is a sigmoid function of the average bit rate over multiple time slots, motivated by video conferencing, and showed that greedy allocation to maximize incremental utility in the current time slot can be implemented in a distributed fashion by an exchange of price and demand amongst users, the network, and an intermediate power allocation module. We proposed resource allocation that considers both the average rate achieved so far and the future expected rate, and showed how the future expected rate can be estimated by modeling the probability that a user will be allocated a subcarrier in a future time slot.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation